Association between epicardial adipose tissue and recurrence after atrial fibrillation catheter ablation. (3rd October 2022) - Lacerda Teixeira, B; Jacinto, S; Silva Cunha, P; Portugal, G; Valente, B; Coutinho Cruz, M; Lousinha, A; Veiga, J; Delgado, A S; Bras, M; Paulo, M; Guerra, C; et al.
Abstract: Introduction: In patients (pts) undergoing atrial fibrillation (AF) catfheter ablation, up to one third have recurrence of atrial fibrillation after a first ablation. Epicardial adipose tissue (EAT) is closely related to AF and could play a role in the recurrence of AF after catheter ablation. Objectives: To analyze the association between EAT and recurrence of AF in pts submitted to ablation. Methods: Single-center retrospective study of consecutive AF pts submitted to ablation between 2011 and 2020, with, at least, one-year follow-up. Epidemiological, clinical, laboratory, echo and angio-CT related data were retrieved. A standardized protocol for quantification of EAT, thoracic adipose volume (TAV) and left atrium volume (LAV) was performed. After comparison of groups using Chi-square and Mann-Whitney analysis, an appropriate Cut Off of EAT for our population was determined, and Kaplan Meier survival curves were used to estimate the risk of events (recurrence of AF). Results: 344 pts (63.1% men) were included, with a mean age of 57.4±10.9 years and a median follow-up time of 22 months. During follow-up, 31., 7% (n=109) of pts had recurrence of AF. Baseline characteristics were similar between groups, except for persistent AF, which was higher in pts with recurrence (25% vs 46%, p=0.011). Recurrence of AF was associated with a higher EAT (p=0.040) and a higher LAV (p<0.001) but not with TAV (p=0.115) nor body mass index (BMI) (p=0.123). In pts with recurrence, values of EAT above a cut-off of 151 cm 3 predict the endpoint of time to recurrence (HR 2.05, CI [1.180–3.566], p=0.01), with these pts presenting a median of 11 months survival free from recurrence, comparing to a median of 15 months in pts with EAT values bellow the aforementioned cut-off (log-rank p=0.008). Conclusion: EAT was predictor of AF recurrence in our population, with pts with a EAT value >151 cm 3 presenting a statistically significant lower survival free from recurrence. Funding Acknowledgement: Type of funding sources: None.